Roles of peripheral clocks: lessons from the fly. - Yildirim, E.; Curtis, R.; Hwangbo, D.S. (FEBS Letters, 2022)
To adapt to and anticipate rhythmic changes in the environment such as daily light-dark and temperature cycles, internal timekeeping mechanisms called biological clocks evolved in a diverse set of organisms, from unicellular bacteria to humans. These biological clocks play critical roles in organisms' fitness and survival by temporally aligning physiological and behavioral processes to the external cues. The central clock is located in a small subset of neurons in the brain and drives daily activity rhythms, whereas most peripheral tissues harbor their own clock systems, which generate metabolic and physiological rhythms. Since the discovery of Drosophila melanogaster clock mutants in the early 1970s, the fruit fly has become an extensively studied model organism to investigate the mechanism and functions of circadian clocks. In this review, we primarily focus on D. melanogaster to survey key discoveries and progresses made over the past two decades in our understanding of peripheral clocks. We discuss physiological roles and molecular mechanisms of peripheral clocks in several different peripheral tissues of the fly.